Pharmacodynamic interactions between muscle relaxants and other medications in practice of anesthesia - Paweł Radkowski; Rafał Marek Okoński (Polish Pharmaceutical Society, 2023)
Knowledge of drug interactions is an essential element of medical practice. Along with the increasing occurrence of multimorbidity and the associated multi-drug use, the number of possible combinations of preparations is constantly rising. The result is a growing number of potentially harmful drug to drug interactions. In their course, the effects of drugs may be enhanced, diminished, or additional effects may emerge that would not occur when used in monotherapy. Taking all of this into consideration, the role of anaesthesiologist in monitoring occurrence of drug interactions appears to be especially important. One should be familiar with drugs used in other fields of medicine and assess their safety in relation to aesthetic agents, the use of which is mainly limited to the conditions of the operating block and intensive care unit. An extremely important part of the modern anaesthesiology and safe conduct of general anaesthesia is the issue of the use of striated muscle relaxants. Due to the wide range of anaesthetic preparations, the aim of this article is to discuss the interactions between depolarizing and nondepolarizing muscle relaxants and other groups of drugs currently used in clinical practice. For this purpose, a review of the literature available in the electronic database of the PubMed portal was conducted. Based on the information obtained, it can be concluded that the effect of muscle relaxants is strongly enhanced when volatile anaesthetics and magnesium ions are used. Whereas neuromuscular relaxation is less intensified by selected groups of antibiotics, lithium ions, statins, and local anaesthetics. Attenuation of the effect occurs with the use of corticosteroids. Antiepileptic drugs, calcium ions, beta-blockers and calcium channel blockers show different effects on the potency of muscle relaxants. Diuretics, angiotensin-converting enzyme inhibitors, anticoagulants and antiplatelet agents have no direct effect on muscle relaxation. The use of corticosteroids does not affect the effectiveness of sugammadex. Sugammadex prolongs the coagulation times [prothrombin (PT) and activated partial thromboplastin (APTT)] in a dose-dependent manner.